Fetal circulating human resistin increases in diabetes during pregnancy and impairs placental mitochondrial biogenesis - Jiang, Shaoning (Mol Med, 2020)
BACKGROUND: Diabetes during pregnancy affects placental mitochondrial content and function, which has the potential to impact fetal development and the long-term health of offspring. Resistin is a peptide hormone originally discovered in mice as an adipocyte-derived factor that induced insulin resistance. In humans, resistin is primarily secreted by monocytes or macrophages. The regulation and roles of human resistin in diabetes during pregnancy remain unclear. METHODS: Fetal resistin levels were measured in cord blood from pregnancies with (n = 42) and without maternal diabetes (n = 81). Secretion of resistin from cord blood mononuclear cells (CBMCs) was measured. The actions of human resistin in mitochondrial biogenesis were determined in placental trophoblastic cells (BeWo cells) or human placental explant. RESULTS: Concentrations of human resistin in cord sera were higher in diabetic pregnancies (67 ng/ml) compared to healthy controls (50 ng/ml, P < 0.05), and correlated (r = 0.4, P = 0.002) with a measure of maternal glycemia (glucose concentration 2 h post challenge). Resistin mRNA was most abundant in cord blood mononuclear cells (CBMCs) compared with placenta and mesenchymal stem cells (MSCs). Secretion of resistin from cultured CBMCs was increased in response to high glucose (25 mM). Exposing BeWo cells or human placental explant to resistin decreased expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), mitochondrial abundance, and ATP production. CONCLUSIONS: Resistin is increased in fetal circulation of infants exposed to the diabetic milieu, potentially reflecting a response of monocytes/macrophages to hyperglycemia and metabolic stresses associated with diabetes during pregnancy. Increased exposure to resistin may contribute to mitochondrial dysfunction and aberrant energy metabolism characteristic of offspring exposed to diabetes in utero.